Sumberdaya manusia Indonesia sebagai penunjang pembangunan jangka panjang - A. Rasyid Baswedan (Economic Journal of Emerging Markets, 1997)
Indonesia has problems in demographicai objects, ie: high growth ofpopulation, low qualityof lifeand unbalance dispersion ofpopulation. More than 30 million of Indonesian people are below the poverty line. Thegrowth of population, speciaiiy for young age, caused many problems in labor. About 60% of Indonesian population live in Java. That is only 7 percent of Indonesian area. This situation had caused many problems in human resource which is very important for development. Unfortunately goverment attention on human resource development is less, that's why any improvements in re-education, re-traning and refunctionare very urgent to be done.. The development of human resouce must be holistic, to include all of humanity aspects. This article shows that the succesful effort of it willbe the key to take off in the long term stage ofIndonesia development